2002
DOI: 10.1124/jpet.301.1.168
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid, a Widely Used Antifibrinolytic Agent, Causes Convulsions by a γ-Aminobutyric AcidA Receptor Antagonistic Effect

Abstract: Application of 4-(aminomethyl)cyclohexanecarboxylic acid (tranexamic acid; TAMCA) to the central nervous system (CNS) has been shown to result in hyperexcitability and convulsions. However, the mechanisms underlying this action are unknown. In the present study, we demonstrate that TAMCA binds to the ␥-aminobutyric acid (GABA) binding site of GABA A receptors in membranes from rat cerebral cortex and does not interfere with N-methyl-D-aspartate receptors. Patch-clamp studies using human embryonic kidney cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
2
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(136 citation statements)
references
References 22 publications
4
124
2
4
Order By: Relevance
“…13 The proposed mechanisms for the cardiac and neurologic manifestations include central sympathetic discharge, GABA A inhibition, and direct cerebral ischemia. [6][7][8][9][10][11]14 In a report similar to ours, a patient was inadvertently given 500 mg intrathecal tranexamic acid and developed convulsions followed by a pulseless electrical activity arrest treated with diazepam, multiple defibrillation attempts, epinephrine, and amiodarone. 6 Her seizures were successfully terminated with diazepam; however, she developed refractory ventricular fibrillation, cardiac collapse and died.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…13 The proposed mechanisms for the cardiac and neurologic manifestations include central sympathetic discharge, GABA A inhibition, and direct cerebral ischemia. [6][7][8][9][10][11]14 In a report similar to ours, a patient was inadvertently given 500 mg intrathecal tranexamic acid and developed convulsions followed by a pulseless electrical activity arrest treated with diazepam, multiple defibrillation attempts, epinephrine, and amiodarone. 6 Her seizures were successfully terminated with diazepam; however, she developed refractory ventricular fibrillation, cardiac collapse and died.…”
Section: Discussionsupporting
confidence: 64%
“…This has been echoed by other authors. 8,14 A third hypothesis is that tranexamic acid causes seizures through direct cerebral hypoperfusion. Mahmoud and Ammar described tranexamic acid 300 mg given accidentally as a spinal dose for lower extremity skin grafting.…”
Section: Discussionmentioning
confidence: 99%
“…13 Tranexamic acid binds competitively, in a dose-dependent fashion, to c-aminobutyric acid (GABA) type A receptors, which results in reduced inhibitory activity and increased neuronal excitation. 14 There are reports of TA causing seizures when in direct contact with the central nervous system in animals 15,16 and humans. 17,18 It is therefore mechanistically plausible that TA is associated with seizures after cardiac surgery.…”
Section: Résumémentioning
confidence: 99%
“…1 Potential mechanisms include direct inhibition of glycine and gamma-aminobutyric acid A (GABAa) receptors as well as direct central nervous system toxicity. 2,3 A recent study showed that TXA inhibits glycine receptors to a greater extent than GABAa receptors and that this effect is attenuated by isoflurane and propofol in vitro. 2 Although these data suggest that propofol and isoflurane may prevent or treat TXA-associated seizures, the optimal management of antiepileptic drugs for TXAassociated seizures in the clinical setting is unclear.…”
Section: To the Editormentioning
confidence: 99%